systems of linear equations
You can solve this by substitution. First, rearrange the first equation to give you u as a function of b:
u = 98 - 2b
Next, substitute this expression in for u in the second equation:
3b + 2(98-2b) = 168
We now have an equation involving only b, so we can simplify and solve for b:
3b + 196 - 4b = 168
-b = -28
b = 28
Now, we can substitute this back into our equation u = 98-2b:
u = 98 - 2(28)
u = 42
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?